Local Stress Analysis on Pipeline End Manifold (PLEM) Due to Pipeline Walking in Subsea Pipeline - Rizki Cahya Illahi; Daniel Mohammad Rosyid; Rudi Walujo Prastianto (International Journal of Offshore and Coastal Engineering, 2026)
The Pipeline End Manifold (PLEM) is a key component in offshore oil and gas subsea systems that serves as a distribution point for fluid flow from subsea pipelines. One phenomenon that can affect its structural integrity is pipeline walking, which is the progressive axial movement of a pipeline caused by pressure and temperature cycles during operation. This study aims to evaluate the effect of pipeline walking on the stress and deformation of a PLEM structure. Numerical modeling was carried out using AutoPIPE to determine the axial displacement of the pipeline, while ANSYS based on the finite element method was used to analyze the structural response of the PLEM. The results show that pipeline walking produces a maximum axial displacement of 78.5994 mm. The maximum Von Mises stress of 61.222 MPa occurred in the 10-inch piping section, while the maximum deformation was 0.1305 mm. These values indicate that the structure remains within safe limits and possesses sufficient stiffness under the analyzed loading conditions.